[tex]\sf \rightarrow y^2 - 3y - 4y +12[/tex]
factor the common term 'y' and '-4'
[tex]\sf \rightarrow y(y - 3) - 4(y - 3)[/tex]
collect into groups
[tex]\sf \rightarrow (y- 4)(y - 3)[/tex]
[tex]\sf \rightarrow 9x^2 - 12x + 4[/tex]
middle term split
[tex]\sf \rightarrow 9x^2 - 6x - 6x+ 4[/tex]
factor the common term '3x' and '-2'
[tex]\sf \rightarrow 3x(3x - 2) -2( 3x-2)[/tex]
collect into groups
[tex]\sf \rightarrow (3x -2)( 3x-2)[/tex]
simplify the following
[tex]\sf \rightarrow (3x -2)^2[/tex]